PENGARUH CONSUMER KNOWLEDGE, BRAND IMAGE, RELIGIUSITAS, DAN LOKASI TERHADAP KEPUTUSAN MENJADI NASABAH PADA BANK SYARIAH - AFRIAN RACHMAWATI (JURNAL EKONOMI SYARIAH, 2020)
This research is aimed at analysing the influence of consumer knowledge, brand image, religiousity, and location to any decision to be sharia bank’s customer by using 4 hypotheses to be examined using SEM method. The research sample includes 212 respondents. Results of SEM analysis meets criteria of goodness of fit index with marginal. Results of this research show that consumer knowledge with product type, product use, and product benefit indicators do not significantly influence the decision to be sharia bank’s customer. Brand image with product attribute, consumer benefit, and brand personality indicators do not significantly influence the decision to be sharia bank’s customer. Religiousity with ritual, ideology, intellectual, experience, and consequence indicators do not significantly influence any decision to be sharia bank’s customer. Location with location accessibility, location smoothness, and location proximity indicators significantly influence any decision to be sharia bank’s customer.